Perancangan Aplikasi Game Edukasi Bahasa Inggris untuk Pembelajaran Anak Usia Dini Berbasis Android : Studi Kasus Sekolah Madrasah Ibtidaiyah An-Nahl, Srengseng, Jakarta Barat - Leonard Christianto Angky; Hani Dewi Ariessanti (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Play can motivate children to achieve various developmental goals and lays a strong foundation for problem-solving skills. Many applications are really helpful for early childhood learning, especially for children who are just starting to recognize numbers and letters, which in turn allows them to be able to read and understand at a higher level. However, the reality is far from parents’ expectations, because many teenagers in society tend to be involved in using social media, while younger children choose game applications that are purely focused on entertainment. As a result, this lack of focus on educational teaching does not contribute to the child’s learning process. Based on observations made at PAUD/RA AMALIA, the learning media used generally still use posters, picture books and some physical toys to increase children’s knowledge and train cognitive and motor skills for children. So from this problem the author wants to apply a strategy to advance the level of learning in early childhood by making educational games based on Android using the Unity application which has multi-platform support with material on recognizing letters and numbers, this game can be played via smartphones/Android owned by people. old, the analytical method used uses PIECES analysis, as well as the game development method used uses the SDLC (System Development Life Cycle) methodology with the Waterfall method. The design method used to describe a system that will be made using the Unified Modeling Language (UML).